Pelatihan Pengembangan Soft Skills Kewirausahaan di Era Digital di SMK Al Mujahidin Cikarang - Siswandi, Arif; Muhidin, Asep; Setyawan, Wisnu (VINICHO MEDIA PUBLISINDO, 2024)
Entrepreneurial soft skills are non-technical skills that are important for entrepreneurs to succeed in managing and developing their businesses. These skills include interpersonal, managerial and personal abilities that help in interacting with other people, making decisions, and adapting to market dynamics and changes in the business environment. By developing entrepreneurial soft skills, entrepreneurs can be better prepared to face business challenges and take advantage of existing opportunities, thereby achieving sustainable success in a competitive business environment. Integrating entrepreneurship soft skills training at Al Mujahidin Vocational School, Cikarang, faces several challenges. However, with the right solution, this training can provide significant benefits for students. It is hoped that the results of this service will provide practical guidance for trainers and consultants who wish to support SMEs in increasing their online presence through social media. With increasing digital competence, it is hoped that SMEs can be more competitive in this increasingly connected global market.